Motherly Care: The impacts of exiting a childcare program on child and maternal health - Boyd, Chris M. (2025)
We investigate the unintended impacts of exiting Peru’s Cuna Más public childcare program on child and maternal health. With increased public childcare use in developing countries, understanding the effects of program exit is critical. We use Cuna Más’ strict age-based graduation rule to identify causal impacts, leveraging comprehensive data from the Demographic and Family Health Survey for the period 2015-2019. Our results suggest that mothers prioritize their children’s health over their own upon program exit. While maternal mental health shows a notable decline, children’s health remains unaffected. These results have important policy implications, highlighting the need for post-program transitional support to mitigate hidden costs for mothers and enhance the positive outcomes children gain during program participation.